Assessment of Awareness of Research Misconduct among Interns in Nigeria - Daha Muhammad; Umar Bello; Fatima Shema; Zakariyya Bello; Paul Gadzama (Mashhad University of Medical Sciences, 2022)
Background: Research is the source of evidence for all medical and allied procedures. Research misconducts are wrongdoings during the conduct of research which can be committed intentionally or ignorantly. Research misconduct includes plagiarism, falsification and fabrication of results. Novice researchers may commit misconduct unaware of it being an unwanted practice. Therefore, this study aimed to assess the awareness of interns of research misconduct.Method: The present study was a cross sectional survey that utilized a questionnaire to obtain information on research misconduct among 53 interns at Federal medical center Yola, Nigeria using a purposive sampling technique. Data analysis was done using SPSS V20 utilizing frequency and percentage to summarize the data and chi-square to assess association between categorical variables.Results: Majority (35.7%) of the participants were within the age range of 26-30. Males were 34 (65.4%) and mostly nurses were 17 (32.5%). Majority of the participants 45 (86.5%) were aware of informed consent but only less than two-fifth (2/5) were aware of declaration of Helsinki. More than 4/5 of the participants were aware of plagiarism (86.8%), fabrication (94.3%) and falsification (86.6%) of results in research.Conclusion: Participants in this study showed a significant level of awareness of research misconduct.